Open‐Shell Donor–Acceptor Conjugated Polymers with High Electrical Conductivity. (4th May 2020) - Huang, Lifeng; Eedugurala, Naresh; Benasco, Anthony; Zhang, Song; Mayer, Kevin S.; Adams, Daniel J.; Fowler, Benjamin; Lockart, Molly M.; Saghayezhian, Mohammad; Tahir, Hamas; King, Eric R.; Morgan, Sarah; et al.
Abstract: Conductive polymers largely derive their electronic functionality from chemical doping, processes by which redox and charge‐transfer reactions form mobile carriers. While decades of research have demonstrated fundamentally new technologies that merge the unique functionality of these materials with the chemical versatility of macromolecules, doping and the resultant material properties are not ideal for many applications. Here, it is demonstrated that open‐shell conjugated polymers comprised of alternating cyclopentadithiophene and thiadiazoloquinoxaline units can achieve high electrical conductivities in their native "undoped" form. Spectroscopic, electrochemical, electron paramagnetic resonance, and magnetic susceptibility measurements demonstrate that this donor–acceptor architecture promotes very narrow bandgaps, strong electronic correlations, high‐spin ground states, and long‐range π‐delocalization. A comparative study of structural variants and processing methodologies demonstrates that the conductivity can be tuned up to 8.18 S cm −1 . This exceeds other neutral narrow bandgap conjugated polymers, many doped polymers, radical conductors, and is comparable to commercial grades of poly(styrene‐sulfonate)‐doped poly(3, 4‐ethylenedioxythiophene). X‐ray and morphological studies trace the high conductivity to rigid backbone conformations emanating from strong π‐interactions and long‐range ordered structures formed through self‐organization that lead to a network of delocalized open‐shell sites in electronic communication. The results offer a new platform for the transport of charge in molecular systems. Abstract : Open‐shell donor–acceptor conjugated polymers comprised of alternating cyclopentadithiophene and thiadiazoloquinoxaline units exhibit narrow bandgaps, strong correlations, long‐range π‐delocalization, and intrinsic electrical conductivities in their native "undoped" form. A comparative study of structural variants and processing methodologies demonstrates that the conductivity can be tuned over orders of magnitude up to 8.18 S cm −1, a record high for an undoped material.